2021
DOI: 10.3389/fpsyt.2021.580843
|View full text |Cite
|
Sign up to set email alerts
|

Online Indicated Preventive Mental Health Interventions for Youth: A Scoping Review

Abstract: Objective: Between the ages of 12 and 25 the onset of mental disorders typically occurs, and the burden of mental health problems is greatest for this group. Indicated preventive interventions to target individuals with subclinical symptoms to prevent the transition to clinical levels of disorders have gained considerable traction. However, the threshold to seek help appears to be high even when help is needed. Online interventions could offer a solution, especially during the COVID-19 pandemic. This scoping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 86 publications
(110 reference statements)
4
21
0
Order By: Relevance
“…Interestingly, however, all studies reported an improvement of mental health symptoms, independent of the length of the intervention (ranging from one session to up to 10 sessions), or type of intervention (online, app, selfadministered, group-based). These findings confirm the ameliorating effects of online/app-based mental health interventions reported in the literature (e.g., [59][60][61][62] ). Given that the pandemic is still ongoing and the overall follow-up period in the included studies is very short, longitudinal results are needed to investigate whether these positive effects can be sustained over time.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, however, all studies reported an improvement of mental health symptoms, independent of the length of the intervention (ranging from one session to up to 10 sessions), or type of intervention (online, app, selfadministered, group-based). These findings confirm the ameliorating effects of online/app-based mental health interventions reported in the literature (e.g., [59][60][61][62] ). Given that the pandemic is still ongoing and the overall follow-up period in the included studies is very short, longitudinal results are needed to investigate whether these positive effects can be sustained over time.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the tools for achieving these goals are already present: online interventions can be an effective and inexpensive alternative or supplement to therapy that is delivered using more traditional modes, overcoming barriers that may prevent people from accessing treatment 79 . The outcome of internet-delivered treatments is generally, but especially in younger people, very promising [59][60][61] . Therefore, available interventions need to be synthesized and structured in an easy and user-friendly manner.…”
Section: Prevention and Intervention: A Synthesizing Websitementioning
confidence: 99%
“…However, there was insufficient recruitment and retention of participants – a personal approach to participant engagement was recommended. Controlled studies are required to increase the effectiveness of CBT in reducing suicidal ideation ( Büscher et al, 2020 ) but it is the most used digital intervention ( Van Doorn et al, 2021 ).…”
Section: Current State Of the Art – Digital Tools And Technologymentioning
confidence: 99%
“…Using a paired samples t-test with 80% power and an alpha of 0.01, we would need a sample of 43 subjects to find similar results. Drop-out rates for digital treatment interventions for young people with beginning mental health complaints have been found to range between 2 and 73% [55]. Inclusion of 125 subjects in the study would give us ample power to investigate our main hypothesis.…”
Section: Sample Sizementioning
confidence: 96%